Cytolysis by CCR5-Using Human Immunodeficiency Virus Type 1 Envelope Glycoproteins Is Dependent on Membrane Fusion and Can Be Inhibited by High Levels of CD4 Expression - LaBonte, Jason A. (American Society for Microbiology, 2003)
T-tropic (X4) and dualtropic (R5X4) human immunodeficiency virus type 1 (HIV-1) envelope glycoproteins kill primary and immortalized CD4(+) CXCR4(+) T cells by mechanisms involving membrane fusion. However, because much of HIV-1 infection in vivo is mediated by M-tropic (R5) viruses whose envelope glycoproteins use CCR5 as a coreceptor, we tested a panel of R5 and R5X4 envelope glycoproteins for their ability to lyse CCR5(+) target cells. As is the case for CXCR4(+) target cells, HIV-1 envelope glycoproteins expressed by single-round HIV-1 vectors killed transduced CD4(+) CCR5(+) cells in a membrane fusion-dependent manner. Furthermore, a CD4-independent R5 HIV-1 envelope glycoprotein was able to kill CD4-negative target cells expressing CCR5, demonstrating that CD4 is not intrinsically required for the induction of death. Interestingly, high levels of CD4 expression protected cells from lysis and syncytium formation mediated by the HIV-1 envelope glycoproteins. Immunoprecipitation experiments showed that high levels of CD4 coexpression inhibited proteolytic processing of the HIV-1 envelope glycoprotein precursor gp160. This inhibition could be overcome by decreasing the CD4 binding ability of gp120. Studies were also undertaken to investigate the ability of virion-bound HIV-1 envelope glycoproteins to kill primary CD4(+) T cells. However, neither X4 nor R5X4 envelope glycoproteins on noninfectious virions caused death in primary CD4(+) T cells. These results demonstrate that the interaction of CCR5 with R5 HIV-1 envelope glycoproteins capable of inducing membrane fusion leads to cell lysis; overexpression of CD4 can inhibit cell killing by limiting envelope glycoprotein processing.